2018
DOI: 10.1242/jcs.220244
|View full text |Cite
|
Sign up to set email alerts
|

Chronic starvation induces non-canonical pro-death stress granules

Abstract: Stress granules (SGs) assemble under stress-induced conditions that inhibit protein synthesis, including phosphorylation of eIF2α, inhibition of the RNA helicase eIF4a proteins or inactivation of mTORC1. Classically defined SGs are composed of translation initiation factors, 40S ribosomes, RNA-binding proteins and poly(A) mRNAs. As such, they represent an important compartment for storage of mRNAs and regulation of their translation. Emerging work on SGs indicates that these structures might promote cellular s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 50 publications
0
45
0
Order By: Relevance
“…However, TIAR‐1 granules exist mainly in the intestine, whereas GTBP‐1 granules could be found in most of the tissues. The differences in the tissue distribution of these two proteins have supported the idea that SGs may have different subtypes (Panas, Ivanov, & Anderson, 2016; Reineke, Cheema, Dubrulle, & Neilson, 2018). Interestingly, we found that tiar‐1 knockdown significantly inhibited the heat‐induced GTBP‐1 granule formation in all tissues, while TIAR‐1 foci could mostly be found in the intestine.…”
Section: Discussionmentioning
confidence: 91%
“…However, TIAR‐1 granules exist mainly in the intestine, whereas GTBP‐1 granules could be found in most of the tissues. The differences in the tissue distribution of these two proteins have supported the idea that SGs may have different subtypes (Panas, Ivanov, & Anderson, 2016; Reineke, Cheema, Dubrulle, & Neilson, 2018). Interestingly, we found that tiar‐1 knockdown significantly inhibited the heat‐induced GTBP‐1 granule formation in all tissues, while TIAR‐1 foci could mostly be found in the intestine.…”
Section: Discussionmentioning
confidence: 91%
“…Evidence for an important role of phosphorylation in the regulation of RNP granule dynamics mainly comes from the observation that inhibition or overexpression of certain kinases leads to altered RNP granule assembly or disassembly (117)(118)(119)(120)(121). In many cases, the involved substrate(s) and underlying molecular mechanisms are still unclear, but there are a few examples from which we can learn about possible mechanisms regarding how phosphorylation may modulate RNP granules: (a) by modulating LLPS of certain RBPs, thus promoting their condensation or decondensation and hence RNP granule assembly or disassembly, and (b) by promoting degradation of certain RBPs (by the proteasome or autophagy), hence reducing their cellular concentration and altering RNP granule assembly or disassembly (Fig.…”
Section: Phosphorylation Regulates the Dynamics Of Rnp Granules Egmentioning
confidence: 99%
“…Besides DYRK3, casein kinase 2 (CK2) was recently found to cause SG disassembly, most likely via phosphorylation of the SG-nucleating protein G3BP1 (119). It has long been known that phosphorylation of G3BP1 on Ser-149 regulates the protein's oligomerization, SG recruitment, and RNase activity (123,124), but only recently was CK2 identified as the kinase that phosphorylates G3BP1 on Ser-149 and thus promotes SG disassembly (119). Whether CK2 also acts on other key SG regulators, such as other SG nucleating RBPs or translation inhibition factors, and hence affects SG dynamics through multiple different mechanisms remains to be examined.…”
Section: Phosphorylation Regulates the Dynamics Of Rnp Granules Egmentioning
confidence: 99%
See 1 more Smart Citation
“…Other potential pro‐metastatic functions include roles in stabilizing oncogenic transcripts , binding of tRNA fragments to mediate cytoprotective oxidative stress‐induced translational repression , and translational activation of the Rho GTPAse‐dependent ROCK1 ser/thr kinase to increase cell motility . We also found that in sarcomas, YB‐1 binds and activates mRNA encoding Ras‐GTPase‐activating protein (SH3 domain) binding protein 1 (G3BP1), a key stress granule (SG) nucleating protein . SGs, mainly studied under oxidative stress, are cytoplasmic aggregates composed of RBPs, the 40S ribosome, stalled translation initiation complexes, and silenced mRNAs that form rapidly under cell stress, and recent studies have begun to uncover the composition of these structures .…”
Section: Introductionmentioning
confidence: 99%